Tempo andante da intervenção urbana: relações temporais nas obras “Imagens posteriores”, “Giganto” e “Polaroides (in)visíveis” - Fernandes, Ana Rita Vidica (2017)
The research “Walking time of urban intervention: temporal relations in the works ‘Imagens Posteriores’, ‘Giganto’ and ‘Polaroids (in)visíveis’ derives from reflections on time in three urban interventions with photography, namely Patricia Gouvêa’s “Imagens Posteriores” (2000-2013), Raquel Brust’s “Giganto” (2009-2013) and Tom Lisboa’s “Polaroides (in)visíveis (2005-2011). I place myself before the images and documents-sign of the works bearing in mind the proposition of the philosopher and historian Georges Didi-Huberman (1998, 2013, 2015), out of which emerges a temporal crossing of past, present and future. This crossing is due to the perception of the lines of time proposed by the philosopher Gilles Deleuze (1987): “time wasted”; “time lost”; “time regained” and “time rediscovered”. Furthermore, it is added the concept of “walking time”, set up by the researcher, concerning the temporal structure that results from the association of “time happening” with “plain space”. The perception of theses times leads to the discussion of the temporal crossings in relation to other urbanity, photography and art images, anachronicaly seen within the works (anachronies-process, anachronies-plasticity, anachronies-form), directed towards the past. And towards the future, at the meeting with the looks in the city (looks-invisibility, looks-emancipation, looks-circulation), it brings out relationship between work, artist, spectator, either in the virtual or in the urban space.